EP882 Risk of ovarian malignancy algorithm performs better than CA125&HE4 alone in a clinical setting. (1st November 2019) - Katsyuba, M; Khasanov, R; Usmanova, G; Akhmetzianova, A; Muratova, G; Saveliev, A; Terenteva, V
Abstract : Introduction/Background: Several studies has shown no advantages of Risk of Ovarian Malignancy Algorithm (ROMA) over CA125 and/or HE4 tumor markers alone when ROC-AUC were analyzed. However, the best way of clinical interpretation of CA125/HE4 levels remains unclear. The goal of the study was to comprehensively evaluate several ways of clinical interpretation of CA125/HE4 serum levels in patients with pelvic mass. Methodology: We analyzed Ca125 and HE4 serum levels in 145 healthy females and in 1019 patients with pelvic mass, scheduled to have surgery. Results: In healthy women 95th percentile (90% Confidence Interval) of HE4 levels were 38.5(37.5–41.2) and 45.8(41.6–48.1) pmol/L in pre- and post-menopause respectively. When the manufacturer's reference limits were used as a threshold, HE4 showed a sensitivity for epithelial ovarian cancer of 54% and a specificity of 98.8%. When our local reference population's reference limits were used, the sensitivity and specificity of HE4 were of 94.7% and of 55.9% respectively. CA125 showed a sensitivity of 96.7% and a specificity of 73.7% according to the 35 U/ml threshold. The sensitivity and specificity of ROMA according to its standard cut-off limits were 89.2 and 88% respectively. Even when calculated optimal cut-off levels of CA125 and HE4 and standard cut-off level for ROMA were used, ROMA showed a tendency to a higher performance and a more balanced sensitivity/specificity than CA125/HE4 alone. Conclusion: Reference limits of CA125/HE4 (not proposed by the manufacturer, not determined in a reference population) do not correspond to the optimal cut-off levels and are not of clinical significance in patients with pelvic mass. ROMA performs better in a clinical setting than CA125/HE4 alone even if optimized cut-off levels (instead of reference limits) of these markers are used. Disclosure: Nothing to disclose.